Korelasi Antara Minat Baca dan Penguasaan Kosa Kata dengan Kemampuan Menulis Pantun - Utami, RR. Sri Hidayati; Amaliah, Nurrohmatul (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This research is a correlational study. The sampling technique is representative by applying a sampling technique. The sampling technique in this study uses probability sampling, a type of simple random sampling. Based on calculations using the Solvin formula, the sample from a population of 150 students amounted to 109. The sample members include fifth-grade students from public elementary schools in the Kenanga cluster area, West Jakarta. The independent variables in this study were reading interest and vocabulary mastery, while the dependent variable was the ability to write rhymes. Methods of data collection using test instruments and questionnaires. Research data analysis using descriptive statistics, correlation tests, and regression tests. Hypothesis testing uses the product moment test assisted by the SPSS program. The results showed that the correlation between interest in reading and ability to write rhymes obtained an r count of 0.766 while the r table with a significance level of 5% for n = 109 was 0.195. From the results of the correlation between vocabulary mastery and the ability to write rhymes, it was obtained that the r count was 0.823, while the r table with a significance level of 5% for n = 109 was 0.195. These results show the value of r count > r table or 0.823 > 0.195. The multiple correlation between reading interest and vocabulary mastery on the ability to write rhymes through multiple correlation testing obtained an R count of 0.865, while the r table at a significance level of 5% and n = 109 was 0.195. The analysis results show that the calculated R-value is greater than the table r value or 0.865 >0.195. This study concludes a positive and significant relationship between reading interest and vocabulary mastery on the ability to write rhymes. The researcher suggests that the school provides supporting facilities for reading activities for their students, including creating a school library and providing a varied collection of books to increase reading interest, which in turn can improve students' vocabulary mastery.